Optical properties of phosphonium-, quaternary ammonium- and imidazolium- substituted regioregular polythiophenes and application for imaging live cells. (November 2019) - Zhang, Chi; Du, Ke; Zhang, Xiangfei; Zheng, Xiaoyu; Cao, Guangxiu; Zhang, Fuli; Feng, Fude
Abstract: Cationic side chains on conjugated polyelectrolytes play crucial roles in the state of polymer chains in water as well as the interactions with live cells. However, it is difficult to compare the effect of different cationic side chains due to the structural defect and severe aggregation issue. We synthesized structurally defined cationic polythiophenes with pendent phosphonium-, quaternary ammonium- and imidazolium-substituted side chains, and confirmed molecularly dispersed state of them in aqueous solutions by spectroscopic characterizations. We also investigated the cytotoxicity as well as cell binding and intracellular trafficking by imaging live cells in the absence and presence of hyaluronic acid. Graphical abstract: Image 1 Highlights: Regioregular polythiophenes with various cations in the side chains are prepared. All of the cationic polythiophenes can be molecularly dissolved in water. Polymers and polymer/HA hybrid complexes are localized in lysosomes and mitochondria after intracellular internalization.